2019
DOI: 10.1111/jgh.14844
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of progression of chronic atrophic gastritis withHelicobacter pyloriand poor prognosis of gastric cancer by CYP3A4

Abstract: Background and Aim It has been well documented that Helicobacter pylori (H. pylori) infection is a risk factor for aggravating gastric mucosal atrophy. However, the exact molecular mechanism mediating this process is not fully elucidated. The purpose of this study was to identify biomarkers, which may predict the risk for progression of chronic atrophic gastritis (CAG) with H. pylori. Methods GSE27411 was downloaded from the Gene Expression Omnibus. The differentially expressed genes (DEGs) between H. pylori‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…These data support the CYP2J2 expression trend observed in other cancerous tissue samples [3]. Interestingly, a new report showed that elevated expression of CYP3A4 could be associated with the progression of chronic atrophic gastritis to gastric cancer and might predict poor prognosis [50]. A recent study has shed some light on the role of CYP2E1 in the development and progression of gastric adenocarcinoma [51].…”
Section: Gastric Cancersupporting
confidence: 67%
“…These data support the CYP2J2 expression trend observed in other cancerous tissue samples [3]. Interestingly, a new report showed that elevated expression of CYP3A4 could be associated with the progression of chronic atrophic gastritis to gastric cancer and might predict poor prognosis [50]. A recent study has shed some light on the role of CYP2E1 in the development and progression of gastric adenocarcinoma [51].…”
Section: Gastric Cancersupporting
confidence: 67%
“…In addition to liver cancer, the dysregulation of CYP3A4 was also found in gastric cancer samples compared with chronic atrophic gastritis cases, which indicates a correlation between CYP3A4 expression and carcinogenic transformation of gastric cancer. 40 Moreover, a similar trend was explored in the influence of CYP2C9 expression. The hepatic CYP2C9 proteins account for nearly 20% of CYP content, and CYP2C9 functions as a major enzyme that participates in the metabolism of various drugs, 41 including warfarin, non-steroidal anti-inflammatory drugs, phenytoin, etc..…”
Section: Discussionmentioning
confidence: 96%
“…CYP3A4 and CYP1A1 are members of the cytochrome P450 superfamily of enzymes. A recent study found that the expression of CYP3A4 might be related to the potential carcinogenic transformation of CAG to GC, which may be biomarkers to predict the progression of CAG and the poor prognosis of GC [ 42 ]. As an isoenzyme of the CYP family I, CYP1A1 mainly participates in the oxidative conversion of the xenobiotics.…”
Section: Discussionmentioning
confidence: 99%